LAFADZ ADZAN DALAM KALIGRAFI ARAB TIGA DIMENSI - ROMEL DINANDA, Syafei, Zubaidah (Universitas Negeri Padang, 2013)
Lafadz Adhan in Arabic calligraphy Final Three Dimensional Works. Arts Education, Faculty of Language and Arts, State University of Padang. Athan has a meaning that is quite deep and has its own charm, which can remind Muslims about time to pray the obligatory prayers. Purpose of this final work is (1) Disclose lafadz prayer in Arabic calligraphy with a 3-dimensional media waste wood. (2) preaching in visual form (Arabic calligraphy 3 dimensions) of wood waste. (3) Reducing the impact of environmental pollution and forest destruction due to waste, into something more useful. Cultivation of this final work using a combination of two techniques, engineering and mechanical engineering continued raft that uses waste wood materials assembled into a three-dimensional works of calligraphy. The title of the work is Lafadz of the adhan itself, such as Allahu Akbar, Allahu Akbar, Allahu Akbar Allahu Akbar. Ash-hadu alla ilaha illallah, ash-hadu alla ilaha illallah. Ash-hadu anna Muhammadan prophet. Ash-hadu anna Muhammadan prophet. Hayya 'base-salat, Hayya' base-prayer. Hayya 'alal-Falah, Hayya' alal-Falah. Allahu akbar Allahu akbar, la ilaha illallah.Kata kunci: lafadz adzan, kaligrafi, limbah kayu